Les enjeux interprétatifs de la prédication averbale dans un corpus narratif : énoncés nominaux et représentation fictionnelle de processus énonciatifs et cognitifs - Bernard Combettes; Annie Kuyumcuyan (Discours)
Autonomous verbless syntactic units are studied in a relatively homogeneous corpus, constituted by the short stories of Maigret’s investigations that G. Simenon wrote from 1930 till 1972. Leaving hyperbate-like adjuncts aside, we deal only with units of autonomous appearance, often constructed as nominal phrases, and we try to clarify their status as verbless sentences or as postponed appositions. The first part of the article examines the description and the role of verbless sentences in narrative, showing how they contribute to create subjectivity effects, in terms of point of view and represented speech. The second part is devoted to appositions. We try to clarify criteria which could differentiate them from nominal sentences as such. This study highlights the decisive role of context and leads to favour the notion of a continuum from nominal sentence to apposition, from main verbless predication to secondary predication.